The Labour Market Development of Oberwart and the Socio-Economic Situation of the Roma - Thomas Leoni (Austrian Institute of Economic Research (WIFO), 2004)
This paper consists of two distinct, yet connected parts. In a previous paper an overview of Roma history in Austria has been presented (Leoni, 2004). The present study can be regarded as a case study that integrates this earlier paper with empirical information1. The largest Austrian Roma community, living in the Burgenland district Oberwart, represents the observed population. A survey of the Roma in Oberwart commissioned by WIFO provides data on the economic situation of this group of people, as well as detailed information on their educational situation and on a number of other social and demographic indicators. This information, coupled with the findings from our historical overview of the Austrian Roma population, helps to gain a better understanding of the Roma and the difficulties that they face. The data that have been collected refer to various aspects of the social and economic life of the Roma; however, the ultimate focus of analysis is represented by the labour market. In fact, the overall goal of the present research project is to foster the social integration of the Roma through the labour market. To this end, not only the supply side, i.e., the Roma and their characteristics, but also the demand side, i.e., the labour market in which they are embedded and with which they are confronted, has to be analysed. Hence, the first chapter of this paper is devoted to an in-depth analysis of the labour market conditions in the Oberwart district, while in the second chapter the findings from the survey are presented.
Keywords: 330; Regionaler Arbeitsmarkt; Roma-Bevölkerung; Ethnische Gruppe; Lebensstandard; Arbeitslosigkeit; Burgenland